Magnesium electrolyte for electrodeposition, and preparation method and application thereof

By introducing tris(2,2,2-trifluoroethyl) borate and aluminum chloride into the electrolyte to form an interface control layer, the contradiction between magnesium foil surface quality and production efficiency was resolved, and efficient and low-cost magnesium foil preparation was achieved.

CN123043589APending Publication Date: 2026-11-06CHONGQING UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611279064.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

The limited dissociation capacity of magnesium salts in existing electrolytes results in low ionic conductivity, severe concentration polarization at high current densities, and poor surface quality of magnesium foil, making it difficult to balance surface quality and production efficiency.

Method used

Tris(2,2,2-trifluoroethyl) borate was used as an additive, combined with aluminum chloride and Grignard magnesium salt, to form a uniform and dense interface control layer, which improved ionic conductivity and suppressed dendrite formation. At the same time, the electrolyte component ratio and stirring conditions were optimized to control the current density at 2~10 mA/cm2.

Benefits of technology

Obtaining a uniform and dense magnesium foil at high current density significantly improves production efficiency, avoids the surface texture problem of rolling, shortens the production process, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123043589A_ABST
    Figure CN123043589A_ABST
Patent Text Reader

Abstract

This invention relates to the field of magnesium electrochemical deposition technology, specifically to a magnesium electrolyte for electrodeposition, its preparation method, and its application. The magnesium electrolyte for electrodeposition comprises a magnesium salt, an organic solvent, and an additive; the additive is tris(2,2,2-trifluoroethyl) borate. The preparation method includes the following steps: S1, dissolving a Grignard magnesium salt in an organic solvent and stirring thoroughly for at least 12 hours under an inert atmosphere to obtain a basic electrolyte; S2, adding tris(2,2,2-trifluoroethyl) borate to the basic electrolyte obtained in step S1 and stirring thoroughly for at least 12 hours under an inert atmosphere to obtain the magnesium electrolyte for electrodeposition. This achieves the goal of obtaining a uniformly dense magnesium foil at a high current density, balancing surface quality and production efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of magnesium electrochemical deposition technology, specifically to a magnesium electrolyte for electrodeposition, its preparation method, and its application. Background Technology

[0002] Magnesium belongs to the hexagonal close-packed (HCP) crystal system, which has fewer active slip systems during room temperature deformation, resulting in significantly lower plastic deformation capacity compared to metals with face-centered cubic structures such as aluminum and copper. When preparing magnesium foil using rolling methods, a strong basal texture is easily formed, limiting the amount of deformation that can be tolerated per pass. This necessitates increasing the number of rolling passes and intermediate annealing processes, making the production process significantly longer than that for aluminum and copper foils. This leads to prominent problems such as low yield, long processing cycle, and high production costs, severely restricting the large-scale preparation and application of ultra-thin magnesium foil.

[0003] Electrodeposition (electrolysis) is a mature method for preparing metal foils, widely used in the industrial production of copper foil, nickel foil, aluminum foil, and other products. Electrodeposition of magnesium foil in an organic electrolyte allows for direct production of the foil under mild conditions, effectively avoiding many problems caused by the poor deformability of magnesium during rolling, such as surface texture limitations, pass restrictions, and low yield. This provides a feasible approach for near-net-shape preparation of magnesium foil.

[0004] However, existing electrolytic magnesium electrolytes primarily use organic solvents such as ethers and esters. These solvents have limited ability to dissociate magnesium salts, resulting in low free ion concentrations and low ionic conductivity in the electrolyte. When using higher current densities to improve production efficiency, concentration polarization at the cathode interface increases significantly, leading to a rough and uneven surface of the resulting magnesium foil, which fails to meet the surface quality requirements of applications. In other words, existing electrolyte systems present a trade-off between surface quality and production efficiency, necessitating improvements at the electrolyte composition level.

[0005] Therefore, developing a novel organic electrolyte with high ionic conductivity, low concentration polarization, and the ability to stably electrodeposit magnesium foil with excellent surface quality at high current densities is of great practical significance. Summary of the Invention

[0006] To address the technical problems of existing organic electrolytic magnesium electrolytes, which suffer from low ionic conductivity, severe concentration polarization at high current densities, and poor surface quality of deposited foils due to the limited dissociation capacity of the solvent for magnesium salts, thus making it difficult to balance surface quality and production efficiency, the present invention aims to provide a magnesium electrolyte for electrodeposition, its preparation method, and its application, so as to obtain a uniform and dense magnesium foil at a higher current density, while balancing surface quality and production efficiency.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0008] In a first aspect, the present invention discloses a magnesium electrolyte for electrodeposition, comprising a magnesium salt, an organic solvent, and an additive; wherein the additive is tris(2,2,2-trifluoroethyl) borate.

[0009] In the above technical solution, the tri(2,2,2-trifluoroethyl) borate ester molecule contains three strongly electron-withdrawing trifluoroethyl groups, giving it high electrochemical reduction activity. During electrodeposition, it preferentially undergoes reduction and decomposition on the cathode surface before magnesium ions, generating a uniform, dense interface control layer rich in fluorides and borides in situ. This interface layer effectively reduces the migration barrier for magnesium ions across the interface, promoting uniform nucleation and directional growth of magnesium ions on the cathode surface and inhibiting the formation of dendrites and loose structures. Furthermore, it blocks continuous side reactions between the electrolyte bulk and the fresh magnesium deposition layer, thereby improving the density and surface smoothness of the deposition layer and significantly improving the surface quality of the magnesium foil.

[0010] Furthermore, the concentration of the tri(2,2,2-trifluoroethyl) borate in the electrolyte is 10~60 g / L.

[0011] In the above technical solutions, when the additive concentration is below 10 g / L, the coverage of the interface control layer formed on the cathode surface is insufficient, limiting its control over magnesium ion deposition behavior and making it difficult to effectively suppress the deterioration of deposition morphology under concentration polarization. When the concentration is above 60 g / L, the electrolyte viscosity increases significantly, the ion migration rate decreases, which in turn exacerbates concentration polarization. At the same time, excessive additives decompose excessively on the cathode surface, generating unnecessary byproducts and reducing current efficiency. Controlling the concentration within the range of 10~60 g / L can achieve a good balance between interface control effect and ion transport efficiency, allowing the electrolyte to maintain stable deposition quality even at higher current densities.

[0012] Furthermore, the magnesium salt is a Grignard magnesium salt, selected from at least one of phenyl magnesium chloride, ethyl magnesium chloride, or butyl magnesium chloride.

[0013] In the above technical solutions, Grignard magnesium salts (RMgX) are classic active magnesium sources in organic electrochemistry. They exhibit high dissociation and electrochemical activity in organic solvents, providing ample reducible magnesium species for the electrolyte. Phenyl magnesium chloride, ethyl magnesium chloride, and butyl magnesium chloride each possess different steric hindrances and electronic effects from their organic groups. They can be flexibly selected or combined according to the requirements of the electrodeposition process, adjusting deposition kinetic parameters to obtain magnesium foil products with different thicknesses and microstructures.

[0014] Furthermore, the electrolyte also includes an auxiliary salt, which is aluminum chloride.

[0015] In the above technical solution, aluminum chloride (AlCl3) is a typical Lewis acid, which can strongly coordinate with chloride ions in Grignard magnesium salts, weakening the Mg-Cl bond and thus promoting further dissociation of magnesium salts. This significantly increases the concentration of free magnesium ions and the ionic conductivity in the electrolyte. The improved ionic conductivity directly reduces the ohmic voltage drop and concentration polarization during electrodeposition, enabling the electrolyte to operate stably at higher current densities. This ensures the surface quality of the deposited foil while improving production efficiency, effectively alleviating the contradiction between surface quality and production efficiency described in the background technology.

[0016] Furthermore, the organic solvent is selected from ether solvents and / or ester solvents.

[0017] In the above technical solutions, ether solvents (such as tetrahydrofuran) have good solubility and coordination stabilizing effect on Grignard magnesium salts, which can ensure the full dissociation and long-term stability of magnesium salts in the electrolyte; ester solvents have a wide electrochemical window and low viscosity, which is beneficial to improving ion migration rate. Ether and ester solvents can be used alone or in combination. By adjusting the ratio of the two, the solubility, ionic conductivity and electrochemical stability of magnesium salts in the electrolyte can be further optimized to adapt to different electrodeposition process conditions.

[0018] Secondly, the present invention discloses a method for preparing a magnesium electrolyte for electrodeposition, comprising the following steps:

[0019] S1. Dissolve Grignard magnesium salt in an organic solvent and stir thoroughly for more than 12 hours under an inert atmosphere to obtain the basic electrolyte;

[0020] S2. Add tris(2,2,2-trifluoroethyl) borate to the basic electrolyte obtained in step S1, and stir thoroughly for more than 12 hours under an inert atmosphere to obtain the magnesium electrolyte for electrodeposition.

[0021] In the above technical solution, a two-step method is used to prepare the electrolyte: first, the Grignard magnesium salt is fully dissolved and dissociated in an organic solvent to form a homogeneous basic electrolyte; then, the additive tris(2,2,2-trifluoroethyl) borate is added and mixed. This order of addition avoids potential localized violent reactions or byproduct formation that may occur when the additive comes into direct contact with the solid magnesium salt, ensuring uniform dispersion and stable performance of the electrolyte components. The stirring time for each step is no less than 12 hours to ensure sufficient dissociation of the magnesium salt and uniform distribution of the additive.

[0022] Furthermore, in steps S1 and S2, the stirring speed is 200~300 rpm.

[0023] In the above technical solutions, when the stirring speed is below 200 rpm, the mixing driving force is insufficient, making it difficult for the electrolyte components to achieve uniform distribution in a short time, thus prolonging the preparation cycle. When the stirring speed is above 300 rpm, excessive mechanical shearing may damage the coordination structure of Grignard magnesium salts, leading to the decomposition or aggregation of active magnesium species, reducing the effective concentration and electrochemical performance of the electrolyte. Controlling the stirring speed between 200 and 300 rpm can achieve a balance between mixing uniformity and component structural integrity.

[0024] Furthermore, the inert atmosphere protection conditions are that both the water content and oxygen content are below 3 ppm.

[0025] In the above technical solution, Grignard magnesium salts are extremely sensitive to trace amounts of water and oxygen: water molecules can undergo irreversible hydrolysis with Grignard reagents, consuming active magnesium species and generating insoluble hydroxide precipitates; oxygen can oxidize Grignard reagents, reducing their electrochemical activity. Strictly controlling the water and oxygen content in the protective atmosphere to below 3 ppm can effectively prevent the above-mentioned side reactions, ensure the concentration and electrochemical activity of active magnesium species in the electrolyte, and guarantee the stability and repeatability of the electrodeposition process.

[0026] Thirdly, the present invention discloses the application of the above-mentioned magnesium electrolyte for electrodeposition or the magnesium electrolyte for electrodeposition prepared by the above-mentioned preparation method in the electrolytic preparation of magnesium foil.

[0027] In the above technical solution, the magnesium electrolyte for electrodeposition is applied to the electrolytic preparation of magnesium foil. By utilizing the regulatory effect of the tri(2,2,2-trifluoroethyl) borate additive on the cathode interface and the effect of the auxiliary salt on the improvement of ionic conductivity, uniform and dense magnesium foil or magnesium alloy foil can be directly obtained under mild electrodeposition conditions without the need for subsequent complex rolling processing steps. The process is short, low-cost, and suitable for the large-scale preparation of ultrathin magnesium foil.

[0028] Furthermore, the application includes the following steps:

[0029] Using a conductive metal as the working electrode and magnesium or a magnesium alloy as the reference electrode and counter electrode, the working electrode, reference electrode and counter electrode are immersed in the magnesium electrolyte for electrodeposition, and magnesium or magnesium alloy foil is electrodeposited on the surface of the working electrode.

[0030] The current density of the electrodeposition is 2~10 mA / cm². 2 .

[0031] In the above technical solution, the current density is less than 2 mA / cm². 2 At times, the deposition rate is too low, and the production efficiency cannot meet actual needs; the current density is higher than 10 mA / cm². 2Even with improved electrolyte ionic conductivity, significant concentration polarization still occurs at the cathode interface, where the magnesium ion supply rate cannot keep up with the electron transfer rate, leading to defects such as dendrites and voids in the deposited layer and a sharp decline in surface quality. Maintaining the current density between 2 and 10 mA / cm² is recommended. 2 Within the scope of this invention, the high ionic conductivity of the electrolyte and the interface regulation effect of the additives can ensure a dense and smooth deposition layer while achieving high production efficiency, effectively resolving the contradiction between surface quality and production efficiency in the prior art.

[0032] The present invention has the following beneficial effects:

[0033] 1. This invention introduces tris(2,2,2-trifluoroethyl) borate as an additive into a Grignard magnesium salt-based electrolyte. By utilizing its preferential reduction on the cathode surface to form a uniform and dense fluorine / boron-containing interface control layer, the nucleation and growth behavior of magnesium ions is effectively controlled, and the formation of dendrites and loose structures is inhibited. This results in a magnesium foil surface that is flat, dense, and uniform, which is significantly better than the control group without the additive.

[0034] 2. The introduction of aluminum chloride as an auxiliary salt in this invention significantly improves the ionic conductivity of the electrolyte and reduces concentration polarization under high current density; combined with the interfacial regulation effect of additives, the electrolyte conductivity is maintained at 2~10 mA / cm². 2 Even at higher current densities, magnesium foil with excellent surface quality can still be obtained, significantly improving production efficiency while ensuring quality.

[0035] 3. This invention directly prepares magnesium foil at room temperature or near room temperature by electrodeposition, effectively avoiding the problems caused by the hexagonal crystal structure of magnesium in the rolling method, such as low basal texture, low deformation per pass, and the need for repeated annealing. This significantly shortens the production process and reduces processing costs.

[0036] 4. This invention uses a two-step method to prepare electrolyte under an inert atmosphere. The operation steps are simple, and the dosage of each component and process parameters (stirring speed, stirring time, atmosphere purity) are clear and controllable. This is conducive to achieving batch stability and consistency of electrolyte and has good prospects for industrial application.

[0037] 5. The magnesium salt of the present invention can be any one or more of phenyl magnesium chloride, ethyl magnesium chloride or butyl magnesium chloride, and the organic solvent can be flexibly selected and matched among ethers and esters. It can be specifically optimized and adjusted according to the thickness, microstructure and mechanical properties of the target foil, and has a wide range of applications. Attached Figure Description

[0038] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention.

[0039] Figure 1 In Example 1 of this invention, the phenyl magnesium chloride electrolyte containing tris(2,2,2-trifluoroethyl) borate was used at a current density of 10 mA / cm². 2 SEM surface morphology of magnesium foil prepared by electrodeposition at 25℃;

[0040] Figure 2 In Example 2 of this invention, the ethyl magnesium chloride electrolyte containing tris(2,2,2-trifluoroethyl) borate was used at a current density of 10 mA / cm². 2 SEM surface morphology of magnesium foil prepared by electrodeposition at 25℃;

[0041] Figure 3 In Example 3 of this invention, the butyl magnesium chloride electrolyte with added tris(2,2,2-trifluoroethyl) borate was used at a current density of 10 mA / cm². 2 SEM surface morphology of magnesium foil prepared by electrodeposition at 25℃;

[0042] Figure 4 In Comparative Example 1 of this invention, the phenyl magnesium chloride electrolyte without additives was tested at a current density of 2 mA / cm². 2 4mA / cm 2 6mA / cm 2 and 10mA / cm 2 Comparison of SEM surface morphology of magnesium foil prepared by electrodeposition at 25℃;

[0043] Figure 5 In Comparative Example 2 of this invention, the ethyl magnesium chloride electrolyte without additives was tested at a current density of 10 mA / cm². 2 SEM surface morphology of magnesium foil prepared by electrodeposition at 25℃;

[0044] Figure 6 In Comparative Example 3 of this invention, the butyl magnesium chloride electrolyte without additives was tested at a current density of 10 mA / cm². 2 SEM image of the surface morphology of magnesium foil prepared by electrodeposition at 25℃. Detailed Implementation

[0045] The technical solution of the present invention will be further described below with reference to embodiments, but it is not limited thereto. Any modifications or equivalent substitutions to the technical solution of the present invention that do not depart from the spirit and scope of the technical solution of the present invention should be covered within the protection scope of the present invention. Process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art; unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available; unless otherwise specified, the technical means used in the embodiments of the present invention are all conventional means well known to those skilled in the art.

[0046] Example 1: A method for preparing a magnesium electrolyte for electrodeposition, comprising the following steps:

[0047] S1. Dissolve Grignard magnesium salt in an organic solvent and stir thoroughly for more than 12 hours under an inert atmosphere to obtain the basic electrolyte.

[0048] Specifically, 0.53 g of anhydrous aluminum chloride was weighed and slowly added to 6 mL of tetrahydrofuran solution. The mixture was stirred at 200-300 rpm for 1 hour to completely dissolve the aluminum chloride. Then, 4 mL of a 2 mol / L phenyl magnesium chloride / tetrahydrofuran solution (Macklin, 99.5% purity, containing molecular sieves) was slowly added dropwise, and the mixture was stirred for another 12 hours to obtain the phenyl magnesium chloride electrolyte.

[0049] During the preparation process, aluminum chloride is first fully dissolved in tetrahydrofuran, and then Grignard magnesium salt solution is slowly added dropwise. This avoids violent exothermic reactions or side reactions caused by excessively high local concentrations, and ensures that the electrolyte composition is uniform and the performance is stable.

[0050] S2. Add tris(2,2,2-trifluoroethyl) borate to the basic electrolyte obtained in step S1, and stir thoroughly for more than 12 hours under an inert atmosphere to obtain the magnesium electrolyte for electrodeposition.

[0051] Specifically, 0.3 g of tris(2,2,2-trifluoroethyl) borate was weighed as an additive and added to 10 mL of the phenyl magnesium chloride electrolyte prepared in step S1. The mixture was stirred for 12 hours under an inert atmosphere to ensure uniform dispersion of the additive, thereby obtaining a magnesium electrolyte for electrodeposition containing the additive with a concentration of approximately 30 g / L.

[0052] The magnesium electrolyte for electrodeposition obtained in step S2 is used for electrolytic magnesium foil, specifically including: using an electrolytic cell apparatus, with a copper sheet as the working electrode, and magnesium as the reference electrode and counter electrode, immersing the working electrode, reference electrode, and counter electrode in the magnesium electrolyte for electrodeposition obtained in step S2, maintaining the electrolyte temperature at 25°C, and setting the current density to 10 mA / cm². 2A constant current electrodeposition experiment was conducted, depositing an electrolytic magnesium foil to a thickness of approximately 10 μm. The surface morphology of the electrolytic magnesium foil sample was observed by SEM, and the results are shown in [reference missing]. Figure 1 .

[0053] Example 2 differs from Example 1 in that the base electrolyte is ethyl magnesium chloride electrolyte. The ethyl magnesium chloride electrolyte is prepared as follows: 0.53 g of anhydrous aluminum chloride is weighed and slowly added to 6 mL of tetrahydrofuran solution. The mixture is stirred at 200-300 rpm for 1 hour to completely dissolve the aluminum chloride. Subsequently, 4 mL of a 2 mol / L ethyl magnesium chloride / tetrahydrofuran solution (Macklin, 99.5% purity, containing molecular sieves) is slowly added dropwise, and stirring continues for 12 hours to obtain the ethyl magnesium chloride electrolyte.

[0054] Similarly, the magnesium electrolyte for electrodeposition prepared in Example 2 was used to electrolyze magnesium foil. The surface morphology of the electrolyzed magnesium foil samples was observed by SEM. The results are shown in [link to relevant documentation]. Figure 2 .

[0055] Example 3 differs from Example 1 in that the base electrolyte is butyl magnesium chloride electrolyte. The preparation of the butyl magnesium chloride electrolyte is as follows: Weigh 0.53 g of anhydrous aluminum chloride and slowly add it to 6 mL of tetrahydrofuran solution. Stir at 200-300 rpm for 1 hour to completely dissolve the aluminum chloride. Then, slowly add 4 mL of a 2 mol / L butyl magnesium chloride / tetrahydrofuran solution (Macklin, 99.5% purity, containing molecular sieves), and continue stirring for 12 hours to obtain the butyl magnesium chloride electrolyte.

[0056] Similarly, the magnesium electrolyte for electrodeposition prepared in Example 3 was used to electrolyze magnesium foil. The surface morphology of the electrolyzed magnesium foil samples was observed by SEM. The results are shown in [link to relevant documentation]. Figure 3 .

[0057] Comparative Example 1: Electrolytic magnesium foil was prepared using a phenyl magnesium chloride electrolyte without additives, wherein the preparation of the phenyl magnesium chloride electrolyte was the same as in Example 1.

[0058] Using a copper sheet as the working electrode and magnesium as the reference and counter electrodes, the working electrode, reference electrode, and counter electrode were immersed in a phenyl magnesium chloride electrolyte at a temperature maintained at 25°C, and subjected to current densities of 2 mA / cm². 2 4mA / cm 2 6mA / cm 2 and 10mA / cm 2 The constant current electrodeposition experiment was conducted, and the deposited foil thickness was approximately 10 μm. The surface morphology of the electrolytic magnesium foil at various current densities was observed by SEM. The results are shown in [reference]. Figure 4 .

[0059] Comparative Example 2: Electrolytic magnesium foil was prepared using an additive-free ethyl magnesium chloride electrolyte. The preparation of the ethyl magnesium chloride electrolyte was the same as in Example 2.

[0060] Using a copper sheet as the working electrode and magnesium as the reference and counter electrode, the working electrode, reference electrode, and counter electrode were immersed in an ethyl magnesium chloride electrolyte at a temperature maintained at 25°C, with a current density of 10 mA / cm². 2 A constant current electrodeposition experiment was conducted, depositing a foil thickness of approximately 10 μm. The surface morphology of the electrolytic magnesium foil was observed using SEM. The results are shown in [reference missing]. Figure 5 .

[0061] Comparative Example 3: Electrolytic magnesium foil was prepared using butyl magnesium chloride electrolyte without additives, wherein the preparation of the butyl magnesium chloride electrolyte was the same as in Example 3.

[0062] Using a copper sheet as the working electrode and magnesium as the reference and counter electrode, the working electrode, reference electrode, and counter electrode were immersed in a butyl magnesium chloride electrolyte at a temperature maintained at 25°C, with a current density of 10 mA / cm². 2 A constant current electrodeposition experiment was conducted, depositing a foil thickness of approximately 10 μm. The surface morphology of the electrolytic magnesium foil was observed using SEM. The results are shown in [reference missing]. Figure 6 .

[0063] See Figure 1 , Figure 2 and Figure 3 Examples 1 (phenyl magnesium chloride system), 2 (ethyl magnesium chloride system), and 3 (butyl magnesium chloride system) with added tris(2,2,2-trifluoroethyl) borate were tested at 10 mA / cm². 2 SEM surface morphology of magnesium foil prepared under high current density. Results show that the three examples at 10 mA / cm²... 2 Magnesium foils prepared under high current density have uniform and flat surfaces, relatively dense structures, and no defects such as delamination or porosity. No large-sized morphological defects were observed in the full field of view of SEM.

[0064] See Figure 4 SEM surface morphology of magnesium foil electrolyzed by the additive-free phenyl magnesium chloride electrolyte in Comparative Example 1 under different current density gradients showed that, limited by the properties of the organic solvent itself, the magnesium foil surface of the additive-free system was relatively smooth only at lower current densities of 2 mA / cm² and 4 mA / cm². When the current density exceeded 4 mA / cm², the surface defects deteriorated sharply, and a disordered lamellar structure appeared. Moreover, the lamellar defects became more and more serious with the increase of current density.

[0065] See Figure 5 and Figure 6The figures show the SEM surface morphology of magnesium foil electrolyzed with electrolytes without additives in Comparative Example 2 (ethyl magnesium chloride system) and Comparative Example 3 (butyl magnesium chloride system) at a current density of 10 mA / cm². The results are similar to those of Comparative Example 1 at high current density: the magnesium deposition layer surface forms a lamellar loose structure with large unevenness and numerous intergranular pores, resulting in severe deterioration of surface quality.

[0066] The results of comparing the examples and the comparative examples show that:

[0067] 1) Limitations of traditional additive-free systems. Traditional additive-free organic electrolytes are limited by the low degree of magnesium salt dissociation and insufficient overall ionic conductivity, and can only operate at levels below 4 mA / cm². 2 The production of magnesium foil with acceptable surface quality under low current density has long been hampered by slow deposition rate and limited production capacity, resulting in a technical challenge of not being able to balance surface quality and production efficiency.

[0068] 2) Interface regulation mechanism of additives. Tris(2,2,2-trifluoroethyl) borate, as a leveling agent, can selectively adsorb onto the highly active deposition sites of magnesium during electrodeposition, balance and regulate the reduction rate of magnesium ions, inhibit the directional growth of coarse grains, effectively weaken the concentration polarization effect under high current density, and fundamentally avoid the formation of loose and lamellar deposition structures, so as to keep the deposition layer dense and flat.

[0069] 3) Significantly widened process operating window. After adding the leveling agent, the ion transport environment inside the electrolyte is optimized, and the electrolysis process operating window is significantly widened: Examples 1 to 3 show a significantly widened operating window at 10 mA / cm². 2 At high current densities, magnesium foils with uniform thickness and intact surfaces can be stably prepared, compared to additive-free systems (which can only be prepared at ≤4mA / cm). 2 This approach not only ensures the production of qualified products but also improves production efficiency, while simultaneously enhancing surface quality and fundamentally resolving the conflict between surface quality and production efficiency.

[0070] The above embodiments are merely preferred embodiments provided to fully illustrate the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are all within the scope of protection of the present invention.

Claims

1. A magnesium electrolyte for electrodeposition, characterized in that, It includes magnesium salts, organic solvents, and additives; the additive is tris(2,2,2-trifluoroethyl) borate.

2. The magnesium electrolyte for electrodeposition according to claim 1, characterized in that, The concentration of the tri(2,2,2-trifluoroethyl) borate in the electrolyte is 10~60 g / L.

3. The magnesium electrolyte for electrodeposition according to claim 1, characterized in that, The magnesium salt is a Grignard magnesium salt, selected from at least one of phenyl magnesium chloride, ethyl magnesium chloride, or butyl magnesium chloride.

4. The magnesium electrolyte for electrodeposition according to claim 3, characterized in that, The electrolyte also includes an auxiliary salt, which is aluminum chloride.

5. The magnesium electrolyte for electrodeposition according to claim 1, characterized in that, The organic solvent is selected from ether solvents and / or ester solvents.

6. A method for preparing a magnesium electrolyte for electrodeposition, characterized in that, Includes the following steps: S1. Dissolve Grignard magnesium salt in an organic solvent and stir thoroughly for more than 12 hours under an inert atmosphere to obtain the basic electrolyte; S2. Add tris(2,2,2-trifluoroethyl) borate to the basic electrolyte obtained in step S1, and stir thoroughly for more than 12 hours under an inert atmosphere to obtain the magnesium electrolyte for electrodeposition.

7. The method for preparing magnesium electrolyte for electrodeposition according to claim 6, characterized in that, In steps S1 and S2, the stirring speed is 200~300 rpm.

8. The method for preparing magnesium electrolyte for electrodeposition according to claim 6, characterized in that, The inert atmosphere protection conditions are that both the water content and oxygen content are below 3 ppm.

9. The application of a magnesium electrolyte for electrodeposition as described in any one of claims 1 to 5 or a magnesium electrolyte for electrodeposition prepared by the preparation method described in any one of claims 6 to 8 in the electrolytic preparation of magnesium foil.

10. The application according to claim 9, characterized in that, Includes the following steps: Using a conductive metal as the working electrode and magnesium or a magnesium alloy as the reference electrode and counter electrode, the working electrode, reference electrode and counter electrode are immersed in the magnesium electrolyte for electrodeposition, and magnesium or magnesium alloy foil is electrodeposited on the surface of the working electrode. The current density of the electrodeposition is 2~10 mA / cm². 2 .